Biocompatible and Sustainable Optical Strain Sensors for Large‐Area Applications. Issue 12 (30th August 2016) - Kamita, Gen; Frka‐Petesic, Bruno; Allard, Antoine; Dargaud, Marielle; King, Katie; Dumanli, Ahu Gumrah; Vignolini, Silvia
Abstract : By a simple two‐step procedure, large photonic strain sensors using a biocompatible cellulose derivative are fabricated. Transient color shifts of the sensors are explained by a theoretical model that consideres the deformation of cholesteric domains, which is in agreement with the experimental results. The extremely simple fabrication method is suitable for both miniaturization and large‐sale manufacture, taking advantage of inexpensive and sustainable materials.